Developing Tourism Digital Dictionary for Persada Husada Indonesia Vocational School in Bekasi - Lutfiyanti, Winda; Romauli, Esterria (PROJECT (Professional Journal of English Education), 2025)
This research aims to design and develop a tourism digital dictionary for students in Persada Husada Indonesia Vocational School in Bekasi. Using Research and Development method, this research was conducted in five stages of ADDIE proposed by Branch (2009) including analysis, design, development, implementation, and evaluation stage. The instruments used are questionnaire, interview, observation, and documentation. The dictionary is developed referring to Jackson (2002) which covers macro (front matter, body, appendices) and micro (arrangement and type of information) structure. The dictionary was validated by two experts both in content and design with no revision which later was implemented in hotel department classes. The result of the implementeation and evaluation from the teachers showed that the dictionary is beneficial not only for students during teaching and learning process but also during internship for self-learning media.